If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26+5x=2x+15
We move all terms to the left:
26+5x-(2x+15)=0
We get rid of parentheses
5x-2x-15+26=0
We add all the numbers together, and all the variables
3x+11=0
We move all terms containing x to the left, all other terms to the right
3x=-11
x=-11/3
x=-3+2/3
| 3^{x+1}=9^x | | 3^(x+1)=9^x | | 6z-20=3z+10 | | 2m(m-3)=0 | | 6z-20=3z+19 | | x-1=(x-2/4) | | 6z-2=3z+10 | | 5(x-1)=x-25 | | 2x-2=3(5x-3)-6 | | 7x=49x² | | 103-x=108 | | 0=(4x-6)/(2x+3) | | -0.25x2+3x+1=0 | | 2+3+3x10=A | | 2(3y-1)+5=6y+4 | | 9x2-10x-16=0 | | 5x+2=x+11 | | (x+8)=3. | | 6x-(x5)=3x+(x-8) | | 3×=80-2x | | 10x=3,90 | | X-0.09x=195850 | | 7(2x-1)+3(x-7)=6 | | 10x+3+2x=5x–4+6x* | | 3a-14=2a-14÷3 | | 2x/7-3=24 | | X-0.09x=374360 | | 5b+2=30 | | 3g(4g+6)=(6g+9) | | x+x+12+2(x+12)=160 | | -3x2+10x-8=0 | | 2x+x+(2x-4)=26 |